Akhlak: Bawaan Lahir atau Hasil Latihan? Sebuah Dialog Kritis antara Pemikiran Islam dan Barat - Indonesia; Muhammad Hidayat; Rahman, Ahmad Sima Hanip; Nasirin, Nasirin; Ansori, Fahmi Moh; Hidayat, Muhammad (NALAR, 2024)
The debate over whether morality is innate (nature) or the result of learning and environment (nurture) is a fundamental discourse in the history of human thought. This article aims to critically and comparatively analyze the views of Islamic and Western thought on the nature of morality. Three main questions are the focus of this study: (1) Is morality permanent, or can it be changed through training?; (2) How are moral laws determined, based on intention or consequence?; and (3) What is the primary source of moral requirements?. This study employs a qualitative approach, utilizing a library research method. Data were collected through documentation techniques from various primary and secondary sources, including books, scientific journals, and relevant philosophical works. The collected data was then analyzed using Miles and Huberman's interactive analysis model, which includes three stages: data reduction, data display, and conclusions. This study reveals that in Islamic thought, morality is viewed as an innate potential that can be shaped and refined through education and self-improvement. Moral judgment is centred on intention (niyyah), with reason and revelation as sources of ethics that work synergistically. Conversely, Western thought tends to debate the fixed or changeable nature of morality, emphasizing the consequences of actions as a moral standard. Within the framework of ethics, rationality and social responsibility are the main foundations for formulating moral standards.